Life cycle assessment of energy crop production with special attention to the establishment of regional biomass utilisation systems. (30th March 2012) - Uchida, Susumu; Hayashi, Kiyotada; Gau, Mitsuru; Kajiyama, Tsutomu; Shirasawa, Shigekiyo; Takahashi, Hiroyuki; Terajima, Yoshifumi; Matsuoka, Makoto; Yoshinaga, Masaru
We conducted a life cycle assessment of energy crop production for bioethanol to clarify the potentialities of biomass utilisation systems in Japan, focusing on cumulative fossil energy demand and global warming potential. Their reductions were evaluated under two scenarios; one was improving cultivation technologies and breeding of new crop varieties, and the other was setting up of regional biomass utilisation systems, in which biomass resources from various industries were utilised mutually and effectively. It was proved that the improvement in cultivation technologies and the establishment of regional biomass utilisation systems have large potential for saving fossil fuel resources and reducing greenhouse gas emissions. Although these results largely depend on scenarios including the lifetime and coverage area of agricultural machinery, and types of biomass utilisation, it was concluded that substitution of petrol by bioethanol converted from these energy crops has considerable potential for rendering our society more sustainable.